Simplifying
(x + 2)(x + -2) = x^{2} + x
Reorder the terms:
(2 + x)(x + -2) = x^{2} + x
Reorder the terms:
(2 + x)(-2 + x) = x^{2} + x
Multiply (2 + x) * (-2 + x)
(2(-2 + x) + x(-2 + x)) = x^{2} + x
((-2 * 2 + x * 2) + x(-2 + x)) = x^{2} + x
((-4 + 2x) + x(-2 + x)) = x^{2} + x
(-4 + 2x + (-2 * x + x * x)) = x^{2} + x
(-4 + 2x + (-2x + x^{2})) = x^{2} + x
Combine like terms: 2x + -2x = 0
(-4 + 0 + x^{2}) = x^{2} + x
(-4 + x^{2}) = x^{2} + x
Reorder the terms:
-4 + x^{2} = x + x^{2}
Add '-1x^{2}' to each side of the equation.
-4 + x^{2} + -1x^{2} = x + x^{2} + -1x^{2}
Combine like terms: x^{2} + -1x^{2} = 0
-4 + 0 = x + x^{2} + -1x^{2}
-4 = x + x^{2} + -1x^{2}
Combine like terms: x^{2} + -1x^{2} = 0
-4 = x + 0
-4 = x
Solving
-4 = x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
-4 + -1x = x + -1x
Combine like terms: x + -1x = 0
-4 + -1x = 0
Add '4' to each side of the equation.
-4 + 4 + -1x = 0 + 4
Combine like terms: -4 + 4 = 0
0 + -1x = 0 + 4
-1x = 0 + 4
Combine like terms: 0 + 4 = 4
-1x = 4
Divide each side by '-1'.
x = -4
Simplifying
x = -4